Gas migration for terrestrial gas hydrates in the Juhugeng mining area of Muli basin, Qilian Mountains, Northwest China. Issue 4 (July 2020) - Wang, Anmin; Li, Jing; Wei, Yingchun; Yang, Chengwei; Nie, Jing; Cao, Daiyong
The Juhugeng mining area in the Qilian Mountains is the only district of China where terrestrial gas hydrate has been found. This paper aimed at studying the gas migration for gas hydrates based on fluid inclusion and apatite fission track experiments with samples being collected in both the hanging wall (Triassic strata, non-hydrocarbon source rocks) and footwall (Jurassic strata, hydrocarbon source rocks) of drilling cores. Fluid inclusions are found in both the hanging wall and footwall, and are characterized by two generations: the first generation includes gaseous and liquid hydrocarbon fluid inclusions with the homogenization temperature of concomitant saline water inclusions being 83–115°C, and the second generation includes gaseous fluid inclusions with the concomitant homogenization temperature of saline water inclusions being 115–149 °C, suggesting two periods of gas migration. Combining with the reconstruction of the burial and thermal histories, the gas migration history can be elaborated as follows: (1) In the Late Paleogene period (>30 Ma), the gas in the footwall migrated to the hanging wall because of the thrusting of Triassic strata, with the temperature being more than 110 ± 10°C (derived from apatite fission track results), corresponding well with the homogenization temperature of the saline water inclusions of the first generation being 115–149 °C; (2) In the Late Neogene to Quaternary (<8 Ma), the study area were impacted by the intensive faults, leading to the second gas migration with a good match between temperature lower than 110 ± 10°C (derived from apatite fission track results) and the homogenization temperature of saline water inclusions in the second generation (83–115 °C), and the geological age of the second gas migration can be restricted from 8 to 1.8 Ma. The permafrost was formed in Quaternary, so the controversial gas hydrate formation pattern can be determined that the gas should be accumulated before the permafrost was formed.